Caracterização dos usuários de crack que não recaem após o tratamento - Ida da Cruz, Joselaine [UNIFESP] (2018)
Introduction: Crack remains a challenge for public health in the area of drugs. Being a drug with intense effects, fast and low cost has been making new users. Understanding this crack user who does not fall after treatment becomes necessary for the development of public policies aimed at their treatment. Objective: To characterize crack users who did not relapse during the abstinence phase, soon after treatment, in the city of São Paulo and Recife. Method: A quantitative study with 700 crack users, both sexes seeking treatment for crack dependence in Clinical Medicine, Therapeutic Communities (CT) and Psychosocial Alcohol and Drug Assistance Center (CAPS AD). The obtained data were analyzed descriptively and for the categorical variables absolute and relative frequencies were presented and for numeric variables, summary measures. The stocks of associations between two categorical variables were verified using the chi-square test, or alternatively in cases of small samples the Fisher's exact test. A significance level of 5% was used for all statistical tests. The statistical software used for the analysis was SPSS 20.0. Logistic regression allowed us to simultaneously identify the effects of demographic characteristics, history of crack use and treatment on the occurrence of non-relapse. Results: Data from 700 crack users were analyzed and a predominance of male users was observed, mean age was 34 years (DP3 = 9.1 years), with a minimum age of 16 years and a maximum age of 62 years of age, evangelical religion (41.4%), unemployed and not looking for a job (35.8%), the main source of employment or spout (42.7%), single love relationship with no fixed relationship (46.3%). After the post-treatment follow-up, it was noted that 7.1% (n = 50) did not present relapses. In the non-relapsed group, there were lower percentages of binge practice (52.0% versus 81.9%), dependency (92.0% vs 98.6%), being absent in life (80.0% % vs. 98.9%) compared to the relapsed group. Singles with a fixed or separated / divorced / widowed relationship presented a non-relapse chance higher than those who had no fixed relationship (3.0 times and 2.8 times, respectively). Conclusion: Data from this research indicate that crack users have a high propensity to relapse into drug use in the first few months after treatment. Marital status, religion, housing, binge, abstinence and dependence are important factors that can lead the user to crack the production of fissure leading to relapse.